The program “National IPO» in Kazakhstan: Opportunities and Risks - Алиева, Б. (Journal of Economic Research & Business Administration, 2017)
This article presents the objectives, opportunities, risks, and examples of the IPO. The experience of the Republic of Kazakhstan in conducting “National IPO» program is ambiguous. Due to the underdevelopment of the stock market, the citizens prefer the banking sector. To change this situation, it is necessary to show the possibility of participation in the IPO. Acquisition gives investors certain rights, but also an additional source of risk. Before deciding to participate in the “National IPO» should carefully evaluate the opportunities and risks. The work is considered one of the most attractive ways of attracting investments for the further development of “People’s IPO». The reasons, goals and objectives of the program “People’s IPO». The work in the analysis of national experience as an example of the IPO, in addition to the main problems identified opportunities and “National IPO» program of proliferation risks. As an example, for the adoption of investor decision on participation in the program “People’s IPO», the dynamics of individual financial indicators of JSC «KEGOC» - the company for the management of the national electric power grid, which is the system operator of the unified electricity system of the country. The mechanism of realization of the IPO and the conclusions. The program “National IPO» has its positive and negative sides. In the future, the future of this program attractive to participate, but this requires the initial impetus to the development of the initiative among the citizens of the future “people’s shareholders.”